E-THeTA: An Efficient and Adaptive TDMA Approach for Wireless Body Area Networks - Herculano, Jorge F.; Andrade, Luís O. S. de; Pereira, Willians De P.; Sá, Alirio S. de (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2024)
Several research efforts have proposed adaptive solutions for Time Division Multiple Access (TDMA) to satisfy time requirements and save energy on Wireless Body Area Networks (WBANs) affected by radiofrequency interferences and carrying dynamic traffic. Even with the benefits, most of these solutions waste network bandwidth, decreasing network performance and the ability to recover from some unexpected communication conditions. This paper introduces the E-THeTA, an adaptive and efficient approach based on TDMA crafted to enhance performance, save energy, and efficiently use WBAN bandwidth. Compared to IEEE 802.15.4 and IEEE 802.15.6 standards and other adaptive approaches, the proposed solution reduces message losses, consumes less energy, and maintains low communication latencies in most evaluated scenarios.